2007
DOI: 10.1080/09540120701203246
|View full text |Cite
|
Sign up to set email alerts
|

Late presentation for HIV care in central Haiti: factors limiting access to care

Abstract: Delays in presentation for HIV care in rural Haiti are linked to demographic, socioeconomic and structural factors, many of which are rooted in poverty. These data suggest that a multifaceted approach is needed to overcome barriers to early presentation for care. This approach might include poverty alleviation strategies; provision of effective, reliable and free medical care; patient outreach through community health workers and collaboration with traditional healers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
22
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 15 publications
7
22
0
Order By: Relevance
“…15,16 In the present study we report similar results, but also found late diagnosis of HIV-1 to be frequent among Antillean and Surinam populations living in The Netherlands. This may indicate that Caribbean sociocultural factors are playing a role in the acknowledgment of risk factors for HIV infection.…”
Section: Discussionsupporting
confidence: 92%
“…15,16 In the present study we report similar results, but also found late diagnosis of HIV-1 to be frequent among Antillean and Surinam populations living in The Netherlands. This may indicate that Caribbean sociocultural factors are playing a role in the acknowledgment of risk factors for HIV infection.…”
Section: Discussionsupporting
confidence: 92%
“…Reports from the U.S. indicate that one-third to nearly half of individuals diagnosed with HIV during client-initiated HIV testing delay entry into care for more than 1 year (Glynn, 2005; Samet et al, 1998). Similar rates of delayed access to care have been observed in developing countries with universal access to HIV care and treatment (Kumar, Kilaru, Kumari, Forde, & Waterman, 2008; Louis, Ivers, Smith Fawzi, Freedberg, & Castro, 2007). …”
supporting
confidence: 63%
“…This is mirrored by the desire of the clients interviewed for availability of food, drugs, and even money to facilitate successful access to health care, while lack of the same were listed as barriers to accessing health care. Low socioeconomic status, poverty, and unemployment have been cited as major reasons for delay in accessing care by HIV-infected patients in previous studies (Joy et al, 2008; Kiwanuka et al, 2008; Louis, Ivers, Smith Fawzi, Freedberg, & Castro, 2007). …”
Section: Discussionmentioning
confidence: 93%